The effect of nano SiO2 on mechanical properties of underwater geopolymer mortar - Tanyildizi, Harun; Coskun, Ahmet; Seloglu, Maksut (Elsevier Sci Ltd, 2023)
This study examined the effect of nano SiO2 on the mechanical properties of underwater geopolymer mortar. The granulated blast furnace slag (GGBS) was selected as the binder in this study. The nano SiO2 was used at 0, 0.5 %, and 1 % by weight of GGBS in the mixtures. Two different casting methods were used in this study. The first casting method was to produce underwater geopolymer mortar samples using the tremie funnel method. The second method was chosen as the method of producing geopolymer mortar samples at room temperature (20 +/- 2 degrees C). The pH test for the wash-out and the slump-flow test for the self-compacting of the underwater geopolymer mortars were carried out. Geopolymer mortar samples were cured underwater and at room temperature for 3, 7, and 28 days at 20 +/- 2 degrees C. Then, ultrasonic pulse velocity, capillary water absorption, and compressive strength tests of the specimens were applied. The results showed that the highest compressive strength among underwater geopolymer mortar samples was obtained from underwater geopolymer mortar containing 0.5 % nano SiO2 with 85.95 MPa. Also, this study found that the underwater geopolymer mortar containing 0.5 % nano SiO2 retained 97.02 % strength of the geopolymer mortar at room temperature.
Keywords: Underwater geopolymer mortar; GGBS; nanoSiO2; Fresh properties; Mechanical properties